Monitoring and Evaluation of Late Functional Outcome in Post-treatment Follow-Up in Clinical Routine Setting - Zebralla, Veit; Meuret, Sylvia; Wiegand, Susanne (Frontiers in Oncology, 2019)
Patients treated for head and neck cancer (HNC) often suffer from severe and visible loss of function as the cancer itself and the side effects of aggressive treatments have the potential to severely affect quality of life. Therefore, the aim of follow up is not only the early detection of potentially curable recurrences and second primary tumors but also the diagnosis and rehabilitation of functional impairments. There are no clear guidelines determining the frequency of follow up visits, and the impact on patient’s prognosis is unclear. An intensive post treatment follow up is needed for the detection of functional impairments and their treatment with the aim of rehabilitating patients to reach their full potential. This article focusses on goals of aftercare treatment and describes the spectrum of long-term sequelae, and the impact of Patient Reported Outcome (PRO) instruments of which three will be introduced.